Pengaruh Model Pembelajaran Cognitive Academic Language Learning Approach Terhadap Minat Membaca Cerita Pendek di Kelas V SD - Setiartin, Titin; Rachman, Ichsan Fauzi; Maryani, Sri (ppjbsip, 2025)
This research explains and explains the application of the Cognitive Academic Language Learning Approach (CALLA) learning model in appreciative reading learning in fifth-grade elementary school. The research uses experiments using quasi-experimental methods. The research controls one variable in the form of matching. Randomized Pretest-Posttest Comparison Group Design, research design using a non-equivalent pre-test and post-test design using the Kolmogorov Smirnov Test. T-test value (calculated t) of two paired samples for the Experiment Class variable (All classes) with the Control Class variable (Karanganyar I). If Sig. (2-tailed) < 0.05, the Sig value is obtained. (2-tailed) = 0.431, meaning the two samples are significantly different. The results of the research show that the CALLA model has a positive effect on increasing the metacognitive, cognitive, and social/affective competencies of 5th-grade elementary school students. The two variables are significantly different through the self-evaluation test. From the two paired sample t-test calculations for the Experiment Class variable (All classes) and the Control Class variable (Karanganyar I), the Sig value was obtained. (2-tailed) = 0.016, meaning the two samples are significantly different. The CALLA learning model is effective in improving the ability to read short stories in reading learning in fifth-grade elementary school.Abstrak Penelitian ini menjelaskan, dan memaparkan penerapan model pembelajaran Cognitive Academic Language Learning Approach (CALLA) dalam pembelajaran membaca apresiatif di kelas V SD. Penelitian menggunakan eksperimen dengan menggunakan metode eksperimen kuasi. Penelitian mengontrol satu variabel dalam bentuk matching. Desain Kelompok Pembanding Prates-Pascates Beracak, desain penelitian menggunakan desain nonekuivalen prates dan pascates dengan menggunakan Kolmogorov Smirnov Test. Nilai Uji-t (t hitung) dua sampel berpasangan untuk variabel Kelas Eksperimen (Seluruh kelas) dengan variabel Kelas Kontrol (Karanganyar I). Jika Sig. (2-tailed) < 0,05 diperoleh hasil nilai Sig. (2-tailed) = 0,431, berarti kedua sampel tersebut berbeda secara signifikan. Hasil penelitian menunjukkan bahwa model CALLA berpengaruh positif terhadap peningkatan kompetensi metakognitif, kognitif, dan sosial/afektif siswa kelas kelas 5 SD. Secara signifikan kedua variabel berbeda melalui tes evaluasi diri. Dari perhitungan Uji-t dua sampel berpasangan untuk variabel Kelas Eksperimen (Seluruh kelas) dengan variabel Kelas Kontrol (Karanganyar I) diperoleh hasil nilai Sig. (2-tailed) = 0,016, berarti kedua sampel tersebut berbeda secara signifikan. Model pembelajaran CALLA efektif meningkatkan kemampuan membaca cerita pendek dalam pembelajaran membaca di kelas V SD.